2007
DOI: 10.1158/1535-7163.mct-06-0691
|View full text |Cite
|
Sign up to set email alerts
|

Identification of molecular characteristics correlated with glioblastoma sensitivity to EGFR kinase inhibition through use of an intracranial xenograft test panel

Abstract: In the current study, we examined a panel of serially passaged glioblastoma xenografts, in the context of an intracranial tumor therapy response model, to identify associations between glioblastoma molecular characteristics and tumor sensitivity to the epidermal growth factor receptor (EGFR) kinase inhibitor erlotinib. From an initial evaluation of 11 distinct glioblastoma xenografts, two erlotinib-sensitive tumors were identified, each having amplified EGFR and expressing wild-type PTEN. One of these tumors e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
210
2
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 182 publications
(227 citation statements)
references
References 26 publications
12
210
2
3
Order By: Relevance
“…In the present study, we found no correlation between the erlotinib-related cellular phenotype and the expression of certain genes (EGFR, PTEN, and AKT1) 5,13,19,23 implicated in modulating GBM cells' response to erlotinib, or proposed to participate in GBM pathogenesis. 11,18,22,27 Although determination of protein phosphorylation was not our goal in the present study, a putative role for these gene products in the response of GBM cells to erlotinib was not evident at the level of gene expression.…”
Section: Discussioncontrasting
confidence: 89%
“…In the present study, we found no correlation between the erlotinib-related cellular phenotype and the expression of certain genes (EGFR, PTEN, and AKT1) 5,13,19,23 implicated in modulating GBM cells' response to erlotinib, or proposed to participate in GBM pathogenesis. 11,18,22,27 Although determination of protein phosphorylation was not our goal in the present study, a putative role for these gene products in the response of GBM cells to erlotinib was not evident at the level of gene expression.…”
Section: Discussioncontrasting
confidence: 89%
“…Finally, on the basis of our findings that FGF signaling can drive phosphorylation of PTEN, we tested the potential for FGF to mediate resistance to EGFR inhibition. Consistent with the observed sensitivity of GBM39 to erlotinib in vivo (34), in the absence of exogenous growth factors treatment of GBM39 cells with erlotinib for 48 h resulted in cell rounding and detachment from the laminin substrate, induction of poly (ADP-ribose) polymerase (PARP) cleavage and loss of viability as measured by WST1 assay, all of which were blocked by the inclusion of bFGF in the medium (Fig. 5 B and C and SI Appendix, Fig.…”
Section: Pten Y240 Phosphorylation Plays a Causative Role In Egfr Tkisupporting
confidence: 80%
“…15) and human glioblastoma xenograft models (16) to allow future patient selection. Several sets of markers with predictive value for response to TKIs were proposed, comprising expression of EGFR, amplification of the EGFR gene, lack of elevated levels of AKT phosphorylation, and absence of EGFRvIII expression (17), whereas another study suggested better response of tumors with expression of EGFRvIII and expression of PTEN (18).…”
Section: Introductionmentioning
confidence: 99%